Biomechanical Stability of Primary and Revision Sacroiliac Joint Fusion Devices: A Cadaveric Study. Issue 1 (January 2022) - Carbone, Jake; Swink, Isaac; Muzzonigro, Thomas; Diehl, Daniel; Oh, Michael; Lindsey, Derek P.; Yerby, Scott; Cheng, Boyle C.
Study Design: An in vitro biomechanics study. Objective: To evaluate the efficacy of triangular titanium implants in providing mechanical stabilization to a sacroiliac joint with primary and revision sized implants. Methods: Ten lumbopelvic cadaveric specimens were tested in 4 stages: intact, pubic symphysis sectioned, primary, and simulated revision. Primary treatment was performed using 3 laterally placed triangular titanium implants. To simulate revision conditions before and after bone ingrowth and ongrowth on the implants, 7.5-mm and 10.75-mm implants were randomly assigned to one side of each specimen during the simulated revision stage. A 6 degrees of freedom spinal loading frame was used to load specimens in 4 directions: flexion extension, lateral bending, axial torsion, and axial compression. Biomechanical evaluation was based on measures of sacroiliac joint rotational and translational motion. Results: Both primary and revision implants showed the ability to reduce translational motion to a level significantly lower than the intact condition when loaded in axial compression. Simulated revision conditions showed no statistically significant differences compared with the primary implant condition, with the exception of flexion-extension range of motion where motions associated with the revised condition were significantly lower. Comparison of rotational and translation motions associated with the 7.5- and 10.75-mm implants showed no significant differences between the treatment conditions. Conclusions: These results indicate that implantation of laterally placed triangular titanium implants significantly reduces the motion of a sacroiliac joint using either the primary and revision sized implants. No statistically significant differences were detected when comparing the efficacy of primary, 7.5-mm revision, or 10.75-mm revision implants.